Brand Positioning Through Celebrity Endorsement - A Review Contribution to Brand Literature - Malik, Abdullah; Sudhakar, Bushan D. (International Review of Management and Marketing, 2014)
The use of celebrities in marketing communications has become the practice of the major companies in the emplacement of the brand in the mind of consumers. Firms are making vast investments in hiring celebrities for positioning of brands by making organizations with endorser qualities such as trustworthiness, attractiveness and expertise. In the backdrop, this paper seeks to explore the variables of brand positioning through sports celebrity endorsement. Secondly, to propose the model through merging the sport celebrity endorsement constructs with brand positioning constructs by drawing together and to develop the scale for measuring brand positioning through celebrity endorsement based on existing literature. Keywords: Brand Positioning; Celebrity Endorsement; Purchase Intention. JEL Classifications: M31; M37; M39